2015
DOI: 10.1111/jep.12436
|View full text |Cite
|
Sign up to set email alerts
|

Indicators based on registers and administrative data for breast cancer: routine evaluation of oncologic care pathway can be implemented

Abstract: It is possible to evaluate the quality of cancer care delivered in clinical practice in recent years, in order to implement interventions aimed to improve adherence to international standards of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 23 publications
(24 reference statements)
3
14
0
Order By: Relevance
“…Moreover, guidelines were not followed for metastatic work-up: imaging was performed too often in early BC (stages I-II) and not enough often in stage III BC. These observations have already been reported in several studies [17,38,39]. Guidelines recommend imaging only for patients with symptomatic early BC and stage III BC because the reported probability of occult distant metastasis in stage I-II BC is exceedingly low (0.3–1.2%) [3,4,38].…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Moreover, guidelines were not followed for metastatic work-up: imaging was performed too often in early BC (stages I-II) and not enough often in stage III BC. These observations have already been reported in several studies [17,38,39]. Guidelines recommend imaging only for patients with symptomatic early BC and stage III BC because the reported probability of occult distant metastasis in stage I-II BC is exceedingly low (0.3–1.2%) [3,4,38].…”
Section: Discussionsupporting
confidence: 53%
“…The recent hospital-based European studies found similar rates (94–98%) [22,23,25,26] while lower rates (92–93%) were observed in the Norwegian and Slovenian population-based [28,29]. Older studies found also lower rates [1113,15,17,20]. In the US, radiotherapy after BCS was less frequent (80%) with geographic disparities [16,34,35].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Their recommendations would fall under the definition of a “less intensive follow-up” that, in the majority of the studies included in our review, would include at least a clinical visit and mammography once a year. However, intensive follow-up is still also quite common in clinical practice [ 48 51 ] and represents a significant workload for radiotherapy, surgery and oncology professionals [ 10 ], in addition to being a costly process.…”
Section: Discussionmentioning
confidence: 99%